Determining Region Boundaries of Critical Commutation Failures in Multi-Infeed HVDC Systems Under Unbalanced Short Circuit Faults - Li, Guoqing; Zhang, Song; Li, Shuguang; Liu, Xianchao; Liu, Xintong (Frontiers in Energy Research, 2021)
This paper presents a region boundaries determination method for critical commutation failures (CF) in multi-infeed high-voltage direct-current (HVDC) systems under unbalanced short circuit faults. By using the nodal impedance matrix, a calculation approach for the converter extinction angles is deduced. First, the extinction angles under unbalanced short circuit faults are calculated. If the extinction angle of a bus is less than the minimum extinction angle, the bus is a failed bus set. By this means, region boundaries of critical commutation failures are demarcated by examining each bus in the AC system. Finally, the effectiveness of the proposed approach was verified by using a modified IEEE 39-bus system.